Multi-Level Analysis of India’s Revocation of Article 370 and Implications for Indo-Pak Relations - Javed Hassan Hashmi; Muhammad Saeed Uzzaman; Azhar Waqar (ASIAN Journal of International Peace & Security (AJIPS), 2021)
This article provides a brief overview of Article 370 and its revocation in order to comprehend the broader political and diplomatic implications for the South Asian region. The paper’s premise is based on an integrative review that focuses on the qualitative nature of data, and it is theoretically inspired by classic realism. The end result suggests that the revocation of Article 370 appears to have had an impact on three levels: at the local level in Kashmir, at the national level in India, and at the inter-state level in terms of India-Pakistan bilateral relations. As per the study, the people of Kashmir have certainly felt endangered for their identity, and even the pro-India Kashmiri political leadership has lost trust in India. Similarly, domestic politics in India are being influenced since this revocation has spurred the Hindutva ideology, which has been emphasizing on supremacy and maximizing of power over other identities. At the interstate level, a persistent trust deficit, trade closures, and deterioration of diplomatic ties became apparent, contributing to the deterioration of India-Pakistan bilateral relations.